Geometric design optimization of a Savonius wind turbine - Torres Espinosa, Sebastian; Marulanda Guerra, Agustín Rafael; Hernández Acevedo, Camilo; Montoya Vallejo, Miguel Fernando (ElSevier, 2022)
Savonius vertical-axis wind turbines are becoming an outstanding alternative for small-scale power generation mainly due to their simple design, high self-starting performance at low wind speeds, omnidirectional capability, and low cost. Over the past few decades, extensive research has suggested turbine configurations that maximize their aerodynamic performance, evaluating different influencing geometric parameters. Nevertheless, few studies have considered running large-scale experimentation, simultaneously assessing different influencing parameters, and implementing mathematical optimization techniques. Consequently, there is a need to establish a set of procedures and techniques that address these gaps. The current research proposes a new design method for a Savonius wind turbine to maximize its aerodynamic performance. The proposed method defines a numerical model for a geometry with four influencing parameters, which automatically achieves solutions to the equations that govern the motion of fluids for different turbines. The model is successfully validated with experimental results available in the literature. The numerical solutions of 340 different turbines build a response surface with excellent quality metrics based on the Kriging technique. Two mathematical optimization techniques are implemented on the response surface to determine the configuration that maximizes its aerodynamic performance. This optimal configuration is characterized under different operating conditions. The results indicate that the optimal turbine has an aspect ratio of 8.38, an overlap ratio of 0.08, a twist angle of 174.05°, and two blades. The behavior shown by the optimal turbine (maximum power coefficient of 0.21 at a wind speed of 12 m/s) is remarkable since its aerodynamic performance is superior to multiple reported turbines. The instantaneous torque that it develops is always positive during its operation, which indicates a greater capacity for self-starting and continuity in its rotation. Likewise, it supplies a maximum rotor power of approximately 160 W at a wind speed of 12 m/s. These results make the optimal turbine an attractive design for electric power generation. The proposed method provides novel insights and powerful tools for researchers to explore various geometries and operating conditions that, together with the established optimization process, accomplish the turbine that maximizes its aerodynamic performance.

Las turbinas eólicas de eje vertical Savonius se están convirtiendo en una alternativa destacada para la generación de energía a pequeña escala, principalmente debido a su diseño simple, alto rendimiento de arranque automático a bajas velocidades del viento, capacidad omnidireccional y bajo costo. Durante las últimas décadas, una amplia investigación ha sugerido configuraciones de turbinas que maximizan su rendimiento aerodinámico, evaluando diferentes parámetros geométricos influyentes. Sin embargo, pocos estudios han considerado realizar experimentos a gran escala, evaluar simultáneamente diferentes parámetros influyentes e implementar técnicas de optimización matemática. En consecuencia, existe la necesidad de establecer un conjunto de procedimientos y técnicas que aborden estas brechas. La investigación actual propone un nuevo método de diseño para una turbina eólica Savonius para maximizar su rendimiento aerodinámico. El método propuesto define un modelo numérico para una geometría con cuatro parámetros influyentes, que logra automáticamente soluciones a las ecuaciones que gobiernan el movimiento de fluidos para diferentes turbinas. El modelo se valida con éxito con resultados experimentales disponibles en la literatura. Las soluciones numéricas de 340 turbinas diferentes construyen una superficie de respuesta con métricas de excelente calidad basadas en la técnica Kriging. Se implementan dos técnicas de optimización matemática sobre la superficie de respuesta para determinar la configuración que maximiza su desempeño aerodinámico. Esta configuración óptima se caracteriza bajo diferentes condiciones de operación. Los resultados indican que la turbina óptima tiene una relación de aspecto de 8.38, una relación de traslape de 0.08, un ángulo de giro de 174.05° y dos aspas. El comportamiento mostrado por la turbina óptima (coeficiente de potencia máxima de 0.21 a una velocidad de viento de 12 m/s) es notable ya que su desempeño aerodinámico es superior a múltiples turbinas reportadas. El torque instantáneo que desarrolla es siempre positivo durante su operación, lo que indica una mayor capacidad de autoarranque y continuidad en su rotación. Asimismo, suministra una potencia máxima de rotor de aproximadamente 160 W a una velocidad de viento de 12 m/s. Estos resultados hacen de la turbina óptima un diseño atractivo para la generación de energía eléctrica. El método propuesto proporciona nuevos conocimientos y poderosas herramientas para que los investigadores exploren diversas geometrías y condiciones de operación que, junto con el proceso de optimización establecido, logren la turbina que maximiza su desempeño aerodinámico.
Keywords: Savonius wind turbine; Computational fluid dynamics; Response surface; Optimization; Performance